Political parties and MPs’ morality policy voting behaviour: evidence from Germany - Engler, Fabian; Dümig, Kathrin (Parliamentary affairs, 2017)
Abstract. This article investigates the impact of party membership on MPs’ morality policy voting behaviour, going beyond the common dichotomy of left and righ